PREPARATION OF A FUTURE MATHEMATICS TEACHER FOR THE IMPLEMENTATION OF THE STEAM APPROACH IN EDUCATION - Ospanova, Н.Б.; Pak, Н.И.; Kamalova, Г.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The STEAM approach in education is one of the global educational trends today. It is based on the integration of science and technology into a single system of education based on interdisciplinary projects. Mathematics in the context of the implementation of the STEAM approach at all levels of education is becoming one of the most significant disciplines and requires the training of a new format teacher with a high level of professional competence for teaching on the basis of STEAM. One of the most effective approaches in preparation of teachers may be the creation of a cluster of academic disciplines that allow meaningful collaboration and common teaching technologies that ensure the optimal formation of future teachers' willingness to implement a new education paradigm. However, an analysis of the education practice and scientific methodological research on the professional training of future bachelor teachers of the "mathematics" profile indicates that at present such training is practically not carried out in the system of teacher education and there are not enough studies that address such issues. The purpose of the work is to substantiate the expediency of training a future bachelor teacher with "mathematics" profile on the basis of a cluster model that organizes the educational process for the most effective formation of his/her willingness to implement the STEM approach in professional activities. Results of the research. A model for training a future bachelor's teacher with "mathematics" profile based on a cluster of disciplines as an integral system was proposed. That includes problem-target, normative-regulatory and organizational, technological, meaningful and productive components; and also an example of cluster of disciplines that contributes to the optimal formation of a teacher's willingness to implement the STEAM approach in education was proposed.